Essential Information about Predatory Publishers and Journals - Beall, Jeffrey (International Higher Education, 2016)
This article introduces, defines, and describes predatory publishers and journals and shows how they hurt science and victimize individual researchers. Academic evaluation that only counts the number of publications may not provide an accurate measure of scholarly achievement, as journals routinely accept papers with little or no peer review.